2021
DOI: 10.3390/ijms22158200
|View full text |Cite
|
Sign up to set email alerts
|

Role of GPR39 in Neurovascular Homeostasis and Disease

Abstract: GPR39, a member of the ghrelin family of G protein-coupled receptors, is zinc-responsive and contributes to the regulation of diverse neurovascular and neurologic functions. Accumulating evidence suggests a role as a homeostatic regulator of neuronal excitability, vascular tone, and the immune response. We review GPR39 structure, function, and signaling, including constitutive activity and biased signaling, and summarize its expression pattern in the central nervous system. We further discuss its recognized ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 122 publications
(283 reference statements)
0
10
0
Order By: Relevance
“…GPR39 has been proposed to play a role in multiple homeostatic processes in the brain, including the balance between neuronal excitation and inhibition, vasodilation and vasoconstriction, and pro- and anti-inflammatory pathways ( Xu et al, 2021 ). GPR39 has also been implicated in a variety of neurological and neuropsychiatric disorders, including AD, depression, anxiety, and seizures ( Laitakari et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GPR39 has been proposed to play a role in multiple homeostatic processes in the brain, including the balance between neuronal excitation and inhibition, vasodilation and vasoconstriction, and pro- and anti-inflammatory pathways ( Xu et al, 2021 ). GPR39 has also been implicated in a variety of neurological and neuropsychiatric disorders, including AD, depression, anxiety, and seizures ( Laitakari et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, while mechanistic inquiries are beyond the scope of the current study, the data presented here is the first description of cognitive impairment in GPR39 KO mice. As discussed in our review article ( Xu et al, 2021 ), specific cellular mediators are being actively investigated and will be pursued in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new therapeutic target in cerebrovascular disease, GPR39 (a member of the ghrelin family of G-protein coupled receptors), is reviewed by Xu et al [13]. They discussed its role in brain and neurovascular homeostasis by maintaining excitatory/inhibitory tone in neural circuits as well as by controlling vascular and inflammatory tone.…”
mentioning
confidence: 99%
“…We recently reported that the G protein-coupled receptor 39 (GPR39) is a dual-ligand receptor regulated by AAderived oxylipins with opposing actions on inflammation and microvascular tone (Xu et al, 2021;Alkayed et al, 2022). GPR39 is a member of the ghrelin family of G proteincoupled receptors (GPCRs) that has recently been implicated in VCI (Davis et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%